STRATEGI PENGEMBANGAN KEBUN KELAPA SAWIT LAHAN GAMBUT KABUPATEN KUBU RAYA - TRIYONO, DJOKO; MUANI, ANI; SAGIMAN, SAERI (Agribusiness Department, Agriculture Faculty, Tanjungpura University, 2015)
Kubu Raya district is a district of the division of Pontianak regency formed by Act 35 of 2007 concerning the Establishment of Kubu Raya district with an area of 6985.20 km ² ( 698,520 acres ) . There are 342.984 ha of peat land area comprising 171 396 ha of shallow peat , peat in the 49 621 ha , 38.953 ha of peat medium , peat in the 83 014 ha while the development activities for oil palm plantations of business licenses obtained has reached an area of about 206 154 ha consisting of 23 fruit companies mostly scattered on peatlands , related to the use of peatlands for oil palm cultivation requires prudence and careful planning with a record of environmental damage . The concept of the development of oil palm plantations on peat land must be in accordance with the rules of Regulation of the Minister of Agriculture of the Republic of Indonesia Number14/Permentan/PL 110/2/2009 on Guidelines for Aquaculture Lowland Sustainable Palm Oil which aims to develop the cultivation of oil palm plantations , preserve the function of land peat , increase production and revenue produksen palm .. To understand these activities , then made the purpose of the study : 1 . Identify and analyze the factors that influence the development strategy of oil palm plantations on peat land in Kubu Raya District .2 . Formulate strategies alternanif development of oil palm plantations on peatland Kubu Raya district .The method used was a survey method and included in the descriptive study . The sampling technique used was purposive sampling method , which determines directly or by deliberately selecting respondents . To know the strengths , opportunities , weaknesses and threats of the development of oil palm plantations on peatland Kubu Raya district , then do a SWOT analysis ( Strengths Weakness Opportunities Threath ) . From the analysis it turned out SO strategy ( Strengths Opportunities) ( 3.3743 ) is the best strategy in the development of oil palm plantations on peatland Kubu Raya district , while the strategy is as follows: 1 ) Planting Area Improvement Strategy and Increased Production of oil palm plantations peatlands . 2 ) Increased and improved palm oil products according to standard .